If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + (x + 6) = -26 + -3x Reorder the terms: 4x + (6 + x) = -26 + -3x Remove parenthesis around (6 + x) 4x + 6 + x = -26 + -3x Reorder the terms: 6 + 4x + x = -26 + -3x Combine like terms: 4x + x = 5x 6 + 5x = -26 + -3x Solving 6 + 5x = -26 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 6 + 5x + 3x = -26 + -3x + 3x Combine like terms: 5x + 3x = 8x 6 + 8x = -26 + -3x + 3x Combine like terms: -3x + 3x = 0 6 + 8x = -26 + 0 6 + 8x = -26 Add '-6' to each side of the equation. 6 + -6 + 8x = -26 + -6 Combine like terms: 6 + -6 = 0 0 + 8x = -26 + -6 8x = -26 + -6 Combine like terms: -26 + -6 = -32 8x = -32 Divide each side by '8'. x = -4 Simplifying x = -4
| 5n-1= | | y=-2(0)-1 | | -y/7=-28 | | 4x+(6x-44)=180 | | 4x+(x+6)=3x-(-26) | | 16(2x-8)=4(8x+5) | | 2p+14=89 | | z+16=-4 | | X+(20+x)=180 | | 2.7(14q+7.2)-3q=9 | | 4(t-3)+8t=6(2t+2)-9 | | 5p=65 | | (X+20)=x | | 14r^3-23r^2+8r=0 | | 30-10n=20 | | -20+10n=40 | | 4e^2x-3=2 | | -10-2n=20 | | 2t+11t=114 | | 4+12p-2=8p+74-4p | | 2+3p=12+2p | | y=2y-2 | | .9w-.6w+.2w=2 | | 8x-9+3x=24 | | 16+2x=50 | | -5x+6=2(x-5)+1 | | 3(2x+10)=108 | | 6x+2(7-x)+10=20 | | (4y+6)-(8+y)=3y-(4y+6) | | 19x+124=48 | | n+14=12-3n | | 4(3.14)5= |